Pengaruh Kepemimpinan, Pendidikan, Motivasi dan Disiplin terhadap Kinerja Karyawan PT. BNI Syariah Kcp Pagar Alam - Abdi Nasrullah (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2021)
The aim of this research is knowing and analyzing the influence of leadership to the employee performance of PT. BNI Syariah KCP Pagar Alam, the influence of education to the employee performance of PT. BNI Syariah KCP Pagar Alam, the influence of motivation to the employee performance of PT. BNI Syariah KCP Pagar Alam, the influence of discipline to the employee performance of PT. BNI Syariah KCP Pagar Alam, the influence of leadership, education, motivation and dicipline to the employee performance of PT. BNI Syariah KCP Pagar Alam. The research is using the primary data and secondary data. Primary data is taken from the questioner which is spread to 58 respondents who is become sample. The technic of data analyzing is using regression linear double from software package of SPSS, this research is using hypothesis. Based on the result of analyzing data, we found that the variables of leadership, education, motivation and discipline have significant relationship to the employee performance of PT. BNI Syariah KCP Pagar Alam.